Agricultural land use conflict management—Vulnerabilities, law restrictions and negotiation frames. A wake-up call. (July 2018) - Petrescu-Mag, Ruxandra Mălina; Petrescu, Dacinia Crina; Azadi, Hossein; Petrescu-Mag, Ioan Valentin
Highlights: The study ascertains and assesses a type of agricultural land use conflict (ALUC). The analyzed land vulnerabilities are: land fragmentation; land grabbing; high natural value farmland disappearance; and scarcity of young farmers. These four items are referred to as latent sources of ALUC, considered a socio-environmental conflict. Several frames of agricultural land are investigated through a survey. Negotiation is identified as viable solution which could use the observed land frames. Abstract: Conflict is part of all societies and conflict management can ensure stability and consistency for communities. This study ascertained and assessed a type of agricultural land use conflict (ALUC) specific to Romania's realities and identified a possible solution for conflict management like negotiation. An original structure of the analysis was developed based on the identification of four latent sources of conflict: land fragmentation; land grabbing; high natural value (HNV) farmland disappearance; and scarcity of young farmers. The paper cast light on several current frames of the agricultural land by investigating the roles that people assigned to it. Frames were studied through a non-probabilistic survey applied on a sample of 170 Romanian land owners. The dominant frame (among the five tested) was the one in which land had an important role in ensuring food safety. Understanding of land frames requires special effort and becomes essential in any situation where participants have different knowledge, values or economic status, as it is the case of conflict management or negotiation process related to agricultural land use. The results stand for awareness of agricultural land frames which should be considered valuable information for equitable land deals in a larger meaning − up to the society scale.